Rosenzweig and Heidegger : between Judaism and German philosophy - Gordon, Peter Eli (Weimar and now, 2003)
Franz Rosenzweig (1886-1929) is widely regarded today as one of the most original and intellectually challenging figures within the so-called renaissance of German-Jewish thought in the Weimar period. The architect of a unique kind of existential theology, and an important influence upon such philosophers as Walter Benjamin, Martin Buber, Leo Strauss, and Emmanuel Levinas, Rosenzweig is remembered chiefly as a "Jewish thinker," often to the neglect of his broader philosophical concerns